Human exposure to toxic metals via contaminated dust: Bio-accumulation trends and their potential risk estimation. (August 2015) - Mohmand, Jawad; Eqani, Syed Ali Musstjab Akber Shah; Fasola, Mauro; Alamdar, Ambreen; Mustafa, Irfan; Ali, Nadeem; Liu, Liangpo; Peng, Siyuan; Shen, Heqing
Highlights: Human exposure to trace metals via dust, in relation to different land use. Trace metal estimation by ICP-MS. Dust as major route of Cd, Pb, Co, Mn and Cr exposure for humans. Potential health risk from exposure to Cd (for children) and Pb via dust. Zn, Cr, Pb, Ni and Cd in hair and nail were beyond the ATSDR threshold. Abstract: We assessed the levels of potentially toxic trace metals, Zinc (Zn), Lead (Pb), Manganese (Mn), Copper (Cu), Nickel (Ni), Chromium (Cr), Cobalt (Co), and Cadmium (Cd), in dust, hair, nail and serum, sampled in rural, urban and industrial areas of Punjab, Pakistan. Trace metals occurrence in all samples, in descending order, was: Zn, Pb, Mn, Cu, Cr, Ni, Co, Cd. The samples from the urban areas showed significantly higher concentration of toxic trace metals (Zn, Ni, Cr, Co, Mn, and Cd) than those from industrial (which conversely had higher levels of Pb and Cu), and than samples from rural areas. Bioaccumulation patterns showed that dust exposure is one of the major routes into human body for Cd, Pb, Co, Mn and Cr, while the burden of Zn, Cu, and Ni can be more linked to dietary sources. The concentrations of trace metals in the samples from Punjab were comparable and/or higher than those reported worldwide. In many cases, the levels of Zn, Cr, Pb, Ni and Cd in hair and nail were beyond the ATSDR threshold guideline values that may cause some serious health effects. Hazard Index (HI) calculated for trace metal concentrations in the human population of Punjab points particularly to health risks from Cd (for children in urban and industrial areas) and from Pb (for all sub-groups).